Evaluation of the quality of business schools - confrontation of existing methodologies and stakeholders' views - Mykytyn, Pavel; Malý, Milan, 1936-; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This paper elaborates on the issues arising during evaluation of quality in tertiary education, specifically in the area of business schools. It provides an overview of theoretical approaches to quality and its measurement, and analyzes current methodologies in quality evaluation of business schools. Part of the thesis consists of results from an inquiry among academics from 4 departments of the Faculty of Business Administration at the University of Economics, Prague, and students of the CEMS International Management program. The results provide a comparison of current practices and stakeholder views, and shows whether these two are in alignment or contradiction.
Vedoucí práce: Milan Malý
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses